2002
DOI: 10.1271/bbb.66.467
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cys Mutation on Taurocholic Acid Transport by Mouse Ileal and Hepatic Sodium-dependent Bile Acid Transporters

Abstract: All cysteines of mouse ileal and hepatic sodiumdependent bile acid transporters (Isbt and Ntcp, respectively) were individually replaced by alanine. Replacement of Cys 106 in Isbt and Cys 96 in Ntcp, which are located closely in alignment, decreased taurocholate uptake. Although Cys 51 in Isbt is conserved in Ntcp, the replacement spoiled Isbt only. Both similarity and diŠerence in the arrangement of functional sites are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 11 publications
(11 reference statements)
4
14
0
Order By: Relevance
“…From these studies, it was suggested that cysteine residues in the hitherto unidentified bile acid carrier proteins are important for substrate binding and translocation. With the molecular identification of NTCP and ASBT, these findings were re-evaluated with an almost complete series of cysteine to alanine mutations in human ASBT , human NTCP (Hallén et al 2000), mouse Asbt and Ntcp (Saeki et al 2002) and rat Ntcp (Zahner et al 2003). Concordantly, these studies identified the conserved cysteine residue C 266 in NTCP/Ntcp and C 270 in ASBT/ Asbt to be the major site where inhibition of bile acid transport activity by thiol reagents is located.…”
Section: Structure-activity Relationships Of the Slc10 Membersmentioning
confidence: 97%
See 1 more Smart Citation
“…From these studies, it was suggested that cysteine residues in the hitherto unidentified bile acid carrier proteins are important for substrate binding and translocation. With the molecular identification of NTCP and ASBT, these findings were re-evaluated with an almost complete series of cysteine to alanine mutations in human ASBT , human NTCP (Hallén et al 2000), mouse Asbt and Ntcp (Saeki et al 2002) and rat Ntcp (Zahner et al 2003). Concordantly, these studies identified the conserved cysteine residue C 266 in NTCP/Ntcp and C 270 in ASBT/ Asbt to be the major site where inhibition of bile acid transport activity by thiol reagents is located.…”
Section: Structure-activity Relationships Of the Slc10 Membersmentioning
confidence: 97%
“…After sitedirected mutagenesis of these cysteins to alanines, the carriers were almost insensitive toward thiophilic inactivation. However, they retained the full transport activity (Hallén et al 2000;Saeki et al 2002;Zahner et al 2003;Banerjee et al 2005). Therefore, it was concluded that C 266 /C 270 is not essential for bile acid transport of NTCP and ASBT by itself, but is located within or near the bile acid-binding pocket of these carriers.…”
Section: Structure-activity Relationships Of the Slc10 Membersmentioning
confidence: 98%
“…This loop is essential for function [207]. Using site directed mutagenesis in conjunction with expression in X. laevis oocytes [349] or COS-7 cells [267], Asp115, Glu257, Cys266 and Cys96, Cys250, Cys266 were found to be functionally essential for rat and mouse Ntcp, respectively.…”
Section: Physiology Of Bile Formationmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] These transporters and their homologous transporters do not share structural similarities with other Na þ -dependent secondary transporters. Even though analysis of naturally occurring and artificially induced mutations has identified some residues critical for the function of these transporters, [8][9][10][11][12][13][14][15][16][17][18][19][20][21] the strict localization of functionally important regions, such as substrate binding sites, has not been decided yet, and the secondary structure of SLC10A1 and SLC10A2 is still controversial. Cys insertion scanning and chemical modification using thiol modifiers are useful methods to determine functionally important regions and the topology of membrane transporters.…”
mentioning
confidence: 99%
“…The multidrug transporter ABCB1, for example, is functional after all the Cys residues are replaced with Ala; thus, Cys-less ABCB1 can be used as a scaffold in Cys-insertion scanning analysis, 27,28) but some Cys residues are essential for the function and correct intracellular localization of both ileal and hepatic SBATs. 1,9,10,12,13,29,30) In addition to considerable similarity between SLC10A1 and SLC10A2 in amino acid sequences (alignment of known mammalian SBATs results in 30% identity and 65% similarity), they share structural similarities, particularly in their hydrophobicity profiles, indicating that their membrane topology is similar. Nevertheless, the distribution of functional regions within the polypeptide chain has been suggested to be different between SLC10A1 and SLC10A2.…”
mentioning
confidence: 99%